Social vulnerability to floods: Review of case studies and implications for measurement - Rufat, Samuel; Tate, Eric; Burton, Christopher G.; Maroof, Abu Sayeed (International journal of disaster risk reduction, 2015)
Abstract A leading challenge in measuring social vulnerability to hazards is for output metrics to better reflect the context in which vulnerability occurs. Through a meta-analysis of 67 flood disaster case studies (1997–2013), this paper profiles the leading drivers of social vulnerability to floods. The results identify demographic characteristics, socioeconomic status, and health as the leading empirical drivers of social vulnerability to damaging flood events. However, risk perception and coping capacity also featured prominently in the case studies, yet these factors tend to be poorly reflected in many social vulnerability indicators. The influence of social vulnerability drivers varied considerably by disaster stage and national setting, highlighting the importance of context in understanding social vulnerability precursors, processes, and outcomes. To help tailor quantitative indicators of social vulnerability to flood contexts, the article concludes with recommendations concerning temporal context, measurability, and indicator interrelationships.
MAG ID: 1947997293

Représentations des risques d’inondation, adaptation et évacuation en Île-de-France - Rufat, Samuel; Comby, Emeline; Santoni, Victor; Plattard, Odile; Lhomme, Serge; Enderlin, Eric (Cybergeo, 2025)
L’étude des déterminants des représentations liées aux risques et leurs effets sur les niveaux de préparation des populations exposées conduit à des conclusions souvent contradictoires d’une étude de cas à une autre. De nombreuses théories et hypothèses concurrentes ont été formulées dans des disciplines différentes, mais aucune n’est parvenue à s’imposer empiriquement. La validation croisée des résultats est complexe et le champ des risk perception s’apparente souvent à une collection d’études de cas indépendantes et peu comparables. À partir d’une enquête par questionnaire sur les représentations liées au risque inondation à Paris et en Île-de-France sur un échantillon de grande taille (n=2976), cet article propose une réflexion théorique et méthodologique pour consolider le positionnement de la géographie dans le champ des représentations des risques, pour mieux démêler les facteurs sociaux et territoriaux. Les questions de recherche se structurent autour du rôle de l’exposition aux aléas, de l’expérience préalable, des situations de vulnérabilité et des territoires de résidence sur les représentations puis sur les comportements. L’hypothèse principale est que les résultats contradictoires publiés dans la littérature internationale pour cerner les déterminants de ces représentations découlent d’approches disciplinaires et de théories divergentes, ainsi que de la place parfois peu assurée de la géographie dans le champ international des risk perception. , The study of risk perception determinants and their impacts on the levels of preparedness of exposed populations often leads to inconclusive results across case studies. Numerous competing theories and hypotheses have been formulated across different disciplines, but their empirical validation remains a challenge. The current fragmentation of research on risk perception hampers the cross-validation of previous results, which might make the field appear as a collection of independent case studies in some instances. We use a flood risk perception and emergency behaviour survey in Paris, France(n=2976), to discuss a theoretical and methodological approach to consolidating the position of geography in the field, better disentangling social and spatial factors. The research questions are structured around the role of hazard exposure, prior experience, place of residence, and social vulnerability on risk perception and emergency behaviour. The main hypothesis is that previous inconclusive results published in the literature on risk perception determinants stem from divergent disciplinary approaches and theories, as well as from the at times uncertain place of geography in the field. , El estudio de las determinantes de la percepción del riesgo y sus efectos sobre los niveles de preparación de la población expuesta, entregan resultados contradictorios según el caso analizado. Si bien han sido propuestas una amplia gama de hipótesis y teorías, éstas restan contrapuestas entre disciplinas y ninguna ha podido prevalecer empíricamente. La validación cruzada de los resultados resulta compleja, y el campo de la percepción del riesgo se asocia generalmente a una colección de estudios de casos independientes y con una baja capacidad de hacerlos comparables. A partir de una encuesta realizada a 2976 personas referente a las representaciones del riesgo de inundación aplicada en la ciudad de París y en la región de Île-de-France, este artículo propone un enfoque teórico y metodológico en vías de consolidar la posición de la geografía en el campo de las representaciones del riesgo, con el fin de dilucidar de manera más robusta los factores sociales y territoriales. Las preguntas de investigación se estructuran en torno al rol de la exposición al peligro, la experiencia previa, las situaciones de vulnerabilidad, el lugar de residencia en las representaciones y los comportamientos. La hipótesis principal expresa que los resultados publicados en la literatura internacional para identificar las determinantes de estas representaciones son contradictorios, lo cuales derivan tanto de enfoques y teorías disciplinariamente divergentes, como del rol en ocasiones incierto que toma la geografía en el ámbito internacional de la percepción del riesgo.
Keywords: Scopus_Alert_26_Septembre_2025